Scientific research on food environments in Brazil: a scoping review - Larissa Loures Mendes; Luana Lara Rocha; Laís Vargas Botelho; Mariana Carvalho de Menezes; Paulo César Pereira de Castro Júnior; Alex Oliveira da Camara; Leticia de Olivera Cardoso; Inês Rugani Ribeiro de Castro; Paula Martins Horta; Milene Cristine Pessoa; Marcela Boro Veiros; Daniela Silva Canella (Cambridge University Press, 2023)
Abstract Objective: To map the scientific research on food environments in Brazil, based on the following questions: How many studies have addressed food environments?; What study designs and methodological approaches were applied?; What is the geographic scope of the studies?; What scenarios and dimensions of food environments were studied?; Which population groups were studied?; How were food environments conceptualised?; What are the main limitations of the studies? Design: Scoping review conducted in four databases, from January 2005 to December 2022, using different food environment-related terms to cover the main types and dimensions proposed in the literature. The studies were independently selected by two authors. A narrative synthesis was used to summarise the findings. Setting: Brazil. Participants: 130 articles. Results: Scientific research on Brazilian food environments has been increasing. The analytical quantitative approach and the cross-sectional design were the most frequently used. Most articles were published in English. The majority of studies evaluated the community food environment, addressed aspects of the physical dimension, sampled the adult population, had food consumption as an outcome, used primary data, and were carried out in capital cities in the Southeast region. Furthermore, in most articles, no conceptual model was explicitly adopted. Conclusions: Gaps in literature are related to the need for conducting studies in the Brazilian countryside, the support for the formulation of research questions based on conceptual models, the use of valid and reliable instruments to collect primary data, in addition to the need for a greater number of longitudinal, intervention and qualitative studies.